We want to simplify the following expression
![(\sin x)/(1-\cos x)](https://img.qammunity.org/2023/formulas/mathematics/college/zoqo0uda4dg8r2tr84nc3zcgpj171vwn9s.png)
We can start by multiplying both numerator and denominator by the conjugate of the denominator:
![\begin{gathered} (\sin(x))/(1-\cos(x))=(\sin(x))/(1-\cos(x))\cdot(1+\cos(x))/(1+\cos(x)) \\ \\ =(\sin(x)(1+\cos(x)))/((1-\cos(x))(1+\cos(x))) \\ \\ =(\sin(x)\cdot(1)+\sin(x)\cdot\cos(x))/((1)\cdot(1)+(1)\cdot(\cos(x))+(-\cos(x))\cdot(1)+(-\cos(x))\cdot(\cos(x))) \\ \\ \begin{equation*} =(\sin(x)+\sin(x)\cos(x))/(1-\cos^2(x)) \end{equation*} \end{gathered}](https://img.qammunity.org/2023/formulas/mathematics/college/1g5obqv0xu369pcqxu0jjebpdza9fgq77a.png)
Then, using the identity
![\sin^2x+\cos^2x=1\implies\sin^2x=1-\cos^2x](https://img.qammunity.org/2023/formulas/mathematics/college/kxve0jzy33v6n4ur3k4mejd1xu6383opy9.png)
We can rewrite our expression as
![(\sin(x)+\sin(x)\cos(x))/(1-\cos^2(x))=(\sin(x)+\sin(x)\cos(x))/(\sin^2(x))=(1)/(\sin x)+(\cos x)/(\sin x)](https://img.qammunity.org/2023/formulas/mathematics/college/f3rhk0cnhmcwl59jyvpmf5o96mtbzsvi2r.png)
By definition of cosecant and cotangent, our expression can be written as
![(1)/(\sin x)+(\cos x)/(\sin x)=\csc x+\cot x](https://img.qammunity.org/2023/formulas/mathematics/college/ti2b9lxe3kbgobqzzna62rl100f191bp24.png)
and this is our answer.
![(\sin x)/(1-\cos x)=\csc x+\cot x](https://img.qammunity.org/2023/formulas/mathematics/college/4ovf0g3z2qq4n31c6v0nutrx8d6bndwsxu.png)